2015
DOI: 10.1155/2016/9076823
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Wnt Receptor Frizzled‐4 in the Human Enteric Nervous System of Infants

Abstract: The Wnt signalling pathway plays a crucial role in the development of the nervous system. This signalling cascade is initiated upon binding of the secreted Wnt ligand to a member of the family of frizzled receptors. In the present study, we analysed the presence of frizzled-4 in the enteric nervous system of human infants. Frizzled-4 could be identified by immunohistochemistry in a subpopulation of enteric neuronal and glial cells in the small and large intestine. Detection of frizzled-4 in the tunica muscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
5
3
0
Order By: Relevance
“…The present study confirmed our previous findings [25] showing the expression of frizzled-4 and p75 NTR in myenteric ganglia in cryosections of the human colon (Figure 1A). We found considerable expression of both markers within the ganglia (also with a large overlap), but no immune-reactivity in surrounding muscle layers.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The present study confirmed our previous findings [25] showing the expression of frizzled-4 and p75 NTR in myenteric ganglia in cryosections of the human colon (Figure 1A). We found considerable expression of both markers within the ganglia (also with a large overlap), but no immune-reactivity in surrounding muscle layers.…”
Section: Resultssupporting
confidence: 93%
“…In order to obtain purified spheroids containing exclusively frizzled-4 positive cells, we stained cell suspensions from human Tunica muscularis with a PE-conjugated anti-frizzled-4 antibody and subsequent used fluorescence-activated cell sorting (FACS). Similar to our previous results by Nothelfer et al [25], we found that frizzled-4 positive cells make up a numerically stable (15.0 ± 7.6% of counts in parent population in five independent patients, Figure 2) and very distinct cell pool, clearly distinguishable from the rest of the Tunica muscularis cell population (Figure 2). As previously shown, these cells are furthermore a subpopulation of the P75 NTRpositive cell population [25], which is commonly used for the isolation of enteric neural progenitors [27,28].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Although a concentration of proliferating neural cells in vitro can be achieved by cell sorting, the combination of markers that will isolate the highest and purest amount of enteric neural progenitors is still unknown. We recently found Fizzled-4, a Wnt receptor, to define a subpopulation of p75-sorted cells [33]. Preliminary data demonstrate that only p75+/Fzd4+, but not p75+/Fzd4− cells proliferate in vitro .…”
Section: Cell Sourcementioning
confidence: 99%